2022
DOI: 10.3389/fonc.2022.879341
|View full text |Cite
|
Sign up to set email alerts
|

Recent and current advances in PET/CT imaging in the field of predicting epidermal growth factor receptor mutations in non-small cell lung cancer

Abstract: Tyrosine kinase inhibitors (TKIs) are a significant treatment strategy for the management of non-small cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) mutation status. Currently, EGFR mutation status is established based on tumor tissue acquired by biopsy or resection, so there is a compelling need to develop non-invasive, rapid, and accurate gene mutation detection methods. Non-invasive molecular imaging, such as positron emission tomography/computed tomography (PET/CT), has been widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Recent studies have shown that non-invasive approaches based on PET/CT, for example, analysis of 18 F-FDG uptake (SUVmax, metabolic volume, tumor lesion glucose) and 18 F-FDG PET/CT-derived radiomics ( 46 , 47 ) could help quantify EGFR mutation status and predict prognosis in lung cancer patients for precision therapy. However, in some previous studies, the results of 18 F-FDG uptake were conflicting ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that non-invasive approaches based on PET/CT, for example, analysis of 18 F-FDG uptake (SUVmax, metabolic volume, tumor lesion glucose) and 18 F-FDG PET/CT-derived radiomics ( 46 , 47 ) could help quantify EGFR mutation status and predict prognosis in lung cancer patients for precision therapy. However, in some previous studies, the results of 18 F-FDG uptake were conflicting ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, 18F-FDG PET/CT radiomics has been applied to multiple aspects of cancer, such as the identification of benign and malignant solitary pulmonary nodules (20), lung cancer pathological typing and staging (21), prediction of gene mutation and molecular phenotypes (22), and evaluation of efficacy and prognosis (23). Amassed evidence substantiates the practicality and promising benefits of 18F-FDG PET/CT radiomics for prognosticating EGFR mutation classifications and subtypes (24). Radiomics methodology significantly mitigates patient discomfort and potential complications while delivering expedited diagnostic feedback and a comprehensive evaluation of tumor heterogeneity (25).…”
Section: Introductionmentioning
confidence: 99%